STRATEGI PENGGUNAAN INSTAGRAM â€œDEWAHOYA COFFEE AND MILKâ€ SEBAGAI MEDIA KOMUNIKASI PEMASARAN TEMPAT NONGKRONG ASIK DI KOTA WATES KABUPATEN KULON PROGO - Kartika, Widyaningtyas Virgo (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACT New media is currently used as an alternative to approach consumers and potential customers. Promotional activities are not only carried out conventionally, but maximize the existence of this new media. Digital Marketing is a marketing activity that uses the internet and information technology to expand and enhance the functions of traditional marketing. Social media with all its advantages and disadvantages give a big role in the marketing communication process. This study discusses the strategy of using Instagram as a marketing communication medium carried out by "Dewahoya Coffee and Milk". The method used in this research is a qualitative method with a case study approach. This study uses in-depth interviews with the owner "Dewahoya Coffee and Milk" as a resource, literature study and documentation. Based on the results of research and discussion, it is known that Instagram utilization planning that has been done is by analyzing the problem, analyzing the audience, setting goals, selecting media and communication channels, and developing plans or activities to achieve the goals. The use of Instagram as a marketing communication medium carried out by "Dewahoya Coffee and Milk" is to utilize the features of photos and videos, comments, caption, location, hashtag and tagging. Evaluation of the use of Instagram is the result of increased sales by attracting more visitors and succeeded in making this place an alternative choice of cool hangouts in Wates City, Kulon Progo Regency.Keywords: Marketing communication, Media Strategy, Instagram, Hangout.